Board Characteristics on ESG Performance: Evidence from Indonesia - Jovita, Gabriella Alodia; Se Tin, Se Tin (School of Accountancy, University of Agung Podomoro, 2025)
The Environmental, Social, and Governance (ESG) framework has become a growing concern for companies worldwide, including those in emerging markets like Indonesia. Despite its recognized benefits, ESG implementation presents challenges and heavily depends on strategic roles of corporate boards. As ESG practices in Indonesia are still at the early stages, board-level decisions play a critical role in shaping sustainable business direction. Grounded in Resource Dependence Theory and Legitimacy Theory, this study aims to expand the literature on board characteristics by examining the influence of two key variables—composite board and board members’ overseas study background—on ESG performance. The research analyzes data from 23 Indonesian listed companies that consistently disclosed ESG-related information through the Refinitiv Database during the 2021-2023 period. Using multiple regression analysis, the findings reveal that both the presence and independent directors and overseas educational background of board members have a significant positive impact on ESG performance. These results provide valuable insights for companies and regulators in formulating governance strategies to enhance sustainability practices.